Tumor-associated macrophages: an effective player of the tumor microenvironment - Basak, Udit; Sarkar, Tania; Mukherjee, Sumon; Chakraborty, Sourio; Dutta, Apratim; Dutta, Saikat; Nayak, Debadatta; Kaushik, Subhash; Das, Tanya; Sa, Gaurisankar (Frontiers in Immunology, 2023)
Cancer progression is primarily caused by interactions between transformed cells and the components of the tumor microenvironment (TME). TAMs (tumor-associated macrophages) make up the majority of the invading immune components, which are further categorized as anti-tumor M1 and pro-tumor M2 subtypes. While M1 is known to have anti-cancer properties, M2 is recognized to extend a protective role to the tumor.As a result, the tumor manipulates the TME in such a way that it induces macrophage infiltration and M1 to M2 switching bias to secure its survival. This M2-TAM bias in the TME promotes cancer cell proliferation, neoangiogenesis, lymphangiogenesis, epithelial to mesenchymal transition, matrix remodeling for metastatic support, and TME manipulation to an immunosuppressive state. TAMs additionally promote the emergence of cancer stem cells (CSCs), which are known for their ability to originate, metastasize, and relapse into tumors. CSCs also help M2-TAM by revealing immune escape and survival strategies during the initiation and relapse phases. This review describes the reasons for immunotherapy failure and thereby, devising better strategies to impair the tumor-TAM crosstalk. This study will shed light on the understudied TAM-mediated tumor progression and address the much-needed holistic approach to anti-cancer therapy, which encompasses targeting cancer cells, CSCs, and TAMs all at the same time.